2020
DOI: 10.3390/su12072592
|View full text |Cite
|
Sign up to set email alerts
|

Constructive Leadership and Employee Innovative Behaviors: A Serial Mediation Model

Abstract: This study aims to examine the influence of constructive leadership practices on the service innovative behaviors of hotel employees by a serial mediation system that treats employee psychological safety and employee creativity as mediators. Empirical data were collected from full-time frontline hotel employees in Antalya, Turkey. By using both convenience and judgmental sampling methods, this study included 357 hotel employees. The results provide empirical evidence for all suggested hypothesized associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 80 publications
(141 reference statements)
1
19
0
3
Order By: Relevance
“…As Ren Zhengfei, President of Huawei, once said, "Talents are not the core competitiveness of Huawei, but the ability to effectively manage talents is the core competitiveness of an enterprise. This is the core talent concept that enables the Huawei team to maintain a high level of creativity, and it is also what we need to learn from now" (Arasli et al, 2020). When it comes to the management of employees, leaders must be involved.…”
Section: Introductionmentioning
confidence: 99%
“…As Ren Zhengfei, President of Huawei, once said, "Talents are not the core competitiveness of Huawei, but the ability to effectively manage talents is the core competitiveness of an enterprise. This is the core talent concept that enables the Huawei team to maintain a high level of creativity, and it is also what we need to learn from now" (Arasli et al, 2020). When it comes to the management of employees, leaders must be involved.…”
Section: Introductionmentioning
confidence: 99%
“…The current study found that psychological safety enhanced work engagement, which prevents the occurrence of employee burnout. This result, coupled with the finding of the aforementioned study 30) that psychological safety enhances work creativity, suggests that improving the psychological safety of fitness club employees has a positive impact on their work environment and the quality of the services provided by them.…”
Section: Psychological Safety Of Fitness Club Employeesmentioning
confidence: 63%
“…A study by Chang et al 29) revealed that employees' emotional exhaustion and burnout are highly correlated with workplace incivility and service climate. Similarly, according to a study conducted on hotel employees 30) , who, similar to fitness club employees, work in the hospitality industry, psychological safety positively influences engagement in creative work tasks and the engagement in creative tasks, in turn, influences the innovative culture of the services provided by these employees.…”
Section: Psychological Safety Of Fitness Club Employeesmentioning
confidence: 99%
“…Such as personality, emotional intelligence, psychological capital, psychological safety, individuals' knowledge and skills [14][15][16][17]. On the other hand, related research suggests that employee creativity is generated by external factors, such as family motivation, management characteristics, constructive leadership, team goal orientation, high-performance work system and organizational climate [18][19][20][21][22][23][24][25][26][27]. In recent years, scholars have begun to pay attention to the impact of new features of the digital era such as social media, information conflict and cooperation models on employee creativity [28][29][30].…”
Section: Introductionmentioning
confidence: 99%